Pelatihan Membuat Website E-Commerce Dengan Weebly.Com Dan Web Blog - Syaikhul Fallah (The Community Engagement Journal, 2020)
E-commerce or could be called electronic trading or e-commerce is the dissemination, purchase, sale, marketing of goods and services through the Internet or a computer network. All elements contained in trading are applied to e-commerce such as customer service, product service, payment method, and promotion way. The creative industry produced by some of the students of the accounting study Program had problems with its marketing. The marketing that is done by one of them still utilizes the sales media by boarding ads on sales sites and social media. They don't yet have their own sales website to market their creative products because of limited insight and expertise and cost to create a sales website. The trainee is a student of accounting study Program. The method performed in this dedication is descriptive. Also, to see how far their knowledge of internet technology is and how and for the sake of what they use the Internet, then do observation and interviews and discussions with the students of accounting study Program by giving Pree test and post-test, and evaluation of the competency of students after training. Thus, the results of the training that from the competency test results can be concluded that the 26 participants who participated in the training were able to understand, know, and explain related e-commerce with weebly.com and web blog in marketing the products it produces.